Successful treatment of HBV, HCV, & HEV, with 12-week long use of tenofovir, sofosbuvir, daclatasvir, and ribavirin: A case report - Braira Wahid (Elsevier, 2020)
Hepatitis C virus (HCV) is the leading cause of morbidity and mortality worldwide. It causes both chronic and acute infections and it has been estimated that about 80% of HCV infected patients develop chronic HCV infection of which 15-30% develop liver complications specifically liver cirrhosis and hepatocellualar carcinoma (HCC). Interferon therapy was previously used standard of care therapy associated with poor efficacy in major proportion of HCV infected population whereas, the recent development of interferon-free therapy or direct-acting antiviral (DAA) drugs are able to achieve sustained virological response (SVR) in 95% of patients. These new drugs are still not properly explored and currently there is minimal clinical experience regarding an efficacious treatment option suitable for triple infection i.e, Hepatitis B virus (HBV), HCV, and Hepatitis E virus (HEV). Here, we suggest well-tolerated sofsobuvir-based treatment regimen in patient infected with HBV, HCV, and HEV. Twelve weeks long treatment with sofsobuvir, daclatasvir, ribavirin, and tenofovir resulted in sustained virological response (SVR) and cleared HBV, HCV, and HEV in diabetic and asthmatic patient. Keywords: HBV, HCV, HEV, Asthma, Diabetes, Sofosbuvir